Optimization of Foreign-related Reception Services for Special Groups in Cruise Tourism - Zhang, Xiaowei; Jiang, Rui (Journal of Social Science and Humanities, 2025)
This study focuses on the optimization of foreign-related reception services for special groups (e.g., elderly tourists, disabled tourists, pregnant women) in cruise tourism. Against the backdrop of global aging and increasing demand for accessible tourism, the paper analyzes shortcomings in current cruise reception services, including language barriers, cultural differences, and inadequate facility adaptability. Based on the SERVQUAL model and Universal Design Theory, a three-dimensional optimization framework — encompassing staff capacity enhancement, hardware facility improvement, and service design innovation—is constructed through questionnaires, case studies, and pilot programs. The results show that strategies such as specialized training, smart navigation system upgrades, and customized itinerary planning can significantly improve service satisfaction among special groups and operational efficiency for cruise companies. This study provides practical insights for the cruise industry to optimize foreign-related reception services and promote accessible tourism development.